Protective doses of tetanus toxoid immunization and its associated factors among mothers in southern Ethiopia - Maycas Gembe; Teklu Wosenyeleh; Wubishet Gezimu (Taylor & Francis Group, 2024)
ABSTRACTThe World Health Organization recommends tetanus toxoid immunization before or during pregnancy for all women of childbearing age. The goal is to reduce maternal and neonatal mortality due to tetanus. According to the 2016 Ethiopia Demographic and Health Survey (EDHS) report, more than half (51%) of women did not receive protective doses of tetanus immunization. To the best of our knowledge, this study uniquely tried to assess the level of protective doses of tetanus toxoid immunization in southern Ethiopia. A community-based cross-sectional study was conducted among 580 randomly selected participants. Variable with p-value of less than .25 in the bivariate analysis were included in the multivariable logistic regression analysis. Finally, statistical significance was declared at a p-value of less than .05. The proportion of protective doses of tetanus toxoid immunization uptake in the area was found to be 41.9% (95% CI: 38-46%). Being enrolled in formal education [AOR = 6.55, 95% CI: 3.23-9.01], having at least two postnatal care visits [AOR = 3.82; 95% CI: 1.78-6.40], having at least four antenatal care visits [AOR = 2.56; 95% CI: 1.41-4.34], and being visited by Health Extension Workers [AOR = 2.66; 95% CI: 1.42-4.01] were found to be factors enhancing the uptake of protective doses of tetanus toxoid immunization. Generally, the uptake or prevalence of the protective doses of tetanus toxoid immunization in the area was lower than the World Health Organization's target. Therefore, all responsible bodies, including healthcare providers, need to strengthen counseling mothers to enhance the uptake of tetanus toxoid immunization.